2022
DOI: 10.3390/diagnostics13010033
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Normative Values to Determine the Prevalence of Biochemical Hyperandrogenism in Premenopausal Women of Different Ethnicities from Eastern Siberia

Abstract: Androgen assessment is a key element for diagnosing polycystic ovary syndrome (PCOS), and defining a “normal” level of circulating androgens is critical for epidemiological studies. We determined the upper normal limits (UNLs) for androgens in a population-based group of premenopausal “healthy control” women, overall and by ethnicity (Caucasian and Asian), in the cross-sectional Eastern Siberia PCOS Epidemiology and Phenotype (ESPEP) Study (СlinicalTrials.gov ID: NCT05194384) conducted in 2016–2019. Overall, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At the same time, prolactin levels were significantly higher (within normative ranges) in Asians as compared to Caucasian women. When studying the impact of ethnicity on androgens, we found that TT, DHAS, and FAI values in the study population were significantly lower in Asians than in Caucasian women, but they were in the normative ranges for the multi-ethnic Siberian population [16]. At the same time, Asians showed lower levels of SHBG (Table S1).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…At the same time, prolactin levels were significantly higher (within normative ranges) in Asians as compared to Caucasian women. When studying the impact of ethnicity on androgens, we found that TT, DHAS, and FAI values in the study population were significantly lower in Asians than in Caucasian women, but they were in the normative ranges for the multi-ethnic Siberian population [16]. At the same time, Asians showed lower levels of SHBG (Table S1).…”
Section: Resultsmentioning
confidence: 81%
“…Study design and population. Study subjects were recruited during the cross-sectional institution-based prospective Eastern Siberia PCOS epidemiology and phenotype (ESPEP) study (ClinicalTrials.gov ID: NCT05194384), conducted in two major areas of Eastern Siberia (the Irkutsk region and the Buryat Republic, Russian Federation) from March 2016 to December 2019, as previously described [15,16]. In brief, a total population of 1490 premenopausal women underwent a mandatory annual employment health assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations